EVALUASI MANAJEMEN BERBASIS SEKOLAH DI SEKOLAH DASAR NEGERI KABUPATEN SEMARANG - Rukayah, Rukayah; Ismanto, Bambang (Universitas Kristen Satya Wacana, 2016)
This study aimed to evaluate the implementation of school based management in SD Negeri Genuk 01 District West Ungaran in terms of context, input, process and product. This study was qualitative evaluative research using CIPP (Context, Input, Process, Product) model of evaluation developed by Stufflebeam. Data collection techniques used were interviews, observation and documentation. Test validity of data using triangulation technique. The results showed that: 1) from the context evaluation, school based management is needed by all stakeholders of the school to improve the quality of education; 2) from the input evaluation, human resources, curriculum, facilities, and funds were sufficient and ready to be used for the implementation of the school based management in primary School Genuk 01; 3) from the process evaluation, the implementation of school based management was not fully in accordance with the plan, especially in the decision making process and the learning process; 4) from the product evaluation, product (output) produced has not been as expected. It is therefore recommended that the school based management program continued with improvements in program implementation process.